Contrasting luxury effect on urban plant phylogenetic and taxonomic diversity in West African cities - Enagnon B. O. Ahouandjinou; Orou G. Gaoue; Moses A. Olutoye; Fabian E. Fassnacht; Appollonia A. Okhimamhe (Ecosystems and People)
Urbanization is a driving factor for biodiversity loss and potential climate change by reducing carbon stocks. Understanding how urban development, as mitigated by socio-economic factors alters urban biodiversity is crucial for effective urban planning that maintains or improves environmental resilience. The luxury effect hypothesis predicts that wealthier parts of a city will have higher levels of biodiversity. This effect has been tested widely but we still have limited understanding of how wealth influences urban biodiversity in tropical regions of developing countries where plant species play profound sociocultural roles beyond aesthetics. This study investigates links between household income and the diversity of cultivated plants distribution within neighborhoods of two growing cities in Benin. We conducted a survey of 936 randomly selected households to record their socioeconomic characteristics and survey the cultivated plant species found in household gardens’. This enabled us to estimate household-level diversity metrics including taxonomic diversity and phylogenetic diversity. We found no global support for the luxury effect on phylogenetic diversity but rented properties had lower plant taxonomic diversity along with less phylogenetic diversity than privately owned houses. Taxonomic diversity is higher in the less urbanized areas while phylogenetic diversity is weakened. Household’s cultural connection to plants has a negative effect on both diversity indices. Our results highlight the complex relationships between socioeconomic traits and urban plant diversity distribution in two tropical African cities, which only partly confirmed the luxury effect hypothesis. Disentangling these complex relationships can help city planners and policymakers to take informed decisions to promote sustainable cities.